Educational Challenges of Adolescents at the Indonesia-Malaysia Border: A Case Study in Vocational School - Nur, Syafrial; Mustikarani, Wini; Nawawi, Nawawi (Universitas Tanjungpura, 2025)
Adolescent education in the Indonesia-Malaysia border region faces complex interrelated challenges. This study explores the conditions of education at SMK Entikong through a qualitative approach, focusing on the real experiences of teachers, students, and the community. The results of the study show that limited physical infrastructure, difficulty in geographical access, shortage of teachers, and socio-economic pressure of the family are the main obstacles to the sustainability of education. Many students have to help their family's economy to the point of being at risk of dropping out of school, while minimal practical facilities cause low job readiness for vocational school graduates. These findings show that the problem of education in border areas cannot be solved with a single approach. Cross-sectoral collaboration and contextual policies are needed to ensure the equitable distribution and sustainability of education in this strategic area.